Effect of Incorporation of whey Protein Concentrate on Quality Characteristic of Buffalo Meat Emulsion Sausage - Ahmad, Saghir; Badpa, Abdolghafour (Journal of Buffalo Science, 2014)
Incorporation of whey protein concentrate (WPC) at a level of 1, 2, 3 and 4% in buffalo meat was investigated for production, quality characteristic of emulsion sausage (ES). Quality of emulsion sausage was evaluated in terms physicochemical characteristics like moisture content, pH, protein content, water holding capacity (WHC), Extract release volume (ERV), microbiological characteristics like total plat count (TPC) and Yeast and mold count, and sensory characteristic including instrumental colour measurement. It was found that moisture content, protein content, ERV and WHC were significantly (P<0.05) increased in emulsion sausage as result of incorporation of 1-4% of WPC. Addition of 1-2% WPC decreased the pH. However 3-4% addition of WPC caused no change in pH and it remained comparable the pH of the control sample. TPC of ES was found in range of 6.23-6.37 log cfu/g. Emulsion sausage incorporated with whey protein concentrate was acceptable to the panelist. The numerical value of ‘L’ for the samples in fresh condition found in the range of 29.50%- 33.25%. Thus sample had 33.25 % of maximum lightness as compared to 66.75% darkness. The sample of fresh emulsion sausages was greyish brown colour in appearance.